PERBEDAAN KENAIKAN BERAT BADAN BAYI YANG DIBERIKAN MAKANAN PADAT PADA USIA 3-5 BULAN DI WILAYAH PUSKESMAS TOMPASOBARU KABUPATEN MINAHASA SELATAN - Rudolf Boyke Purba; Olfie Sahelangi; Linda Liando (POLTEKKES KEMENKES MANADO, 2013)
Breast milk is the best food for babies, and complementary foods or solid foods is atransition from breast milk food given during a short period ie 4-6 months of age , becauseof the growing baby need energy and nutrients that exceed the amount obtained from ASI.This study aimed to determine differences in weight gain infants given solid foods at theage of 3-5 months in the Work Area Health Center Tompasobaru South MinahasaRegency. This type of study is a prospective observational cohort design .The timing ofthe months of December 2012 through March 2013. The subjects were families withbabies aged 3-5 months with a sample of 57 infants. Data were collected using aquestionnaire that was available and the data weight gain obtained by using the directweighing steelyard. Processing and data analysis using t-test. The results showed anaverage weight loss in the group that first month of breastfeeding eskluisif 6.0 kg , 6.77 kgof the second month , third month of 7.21 kg. Group given solid foods first month weight5.68 kg , 6.27 kg of the second month, third month of 6.75 kg . In the first month there wasno significant difference in body weight ( p> 0.05 ) . In both there is a significant differencein body weight ( p< 0.05 ) . In the third month there was no significant difference in bodyweight ( p< 0.05 ) . Average weight gain the first month exclusively breastfed 0.66 kg ,4.44 kg of the second month . Group who received solid foods first month of 0.59 kg , 0.48kg of the second month . Conclusion there is no difference in significant weight gain ininfants who were exclusively breastfed babies who received solid foods in infants aged 3-5months in Regional Health Center Tompasobaru